(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Starting from the analysis of the different norms of the Italian Constitution concerning science, the essay examines which spaces and limits scientific operators, legislators, judges and the Constitutional Court encounter when dealing with scientific activities or disciplines. It also examines a series of pronouncements in which the Constitutional Court seems to have adopted very different approaches (for example, on the subject of animal experimentation or the use of embryos for scientific purposes).